Adolescents and Emotions: A Literature Review on the Influence of Emotional Intelligence on Adolescent Mental Well-Being - Rudy Pratama (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Trait emotional intelligence is considered an essential aspect that helps adolescents understand and regulate their emotional experiences, especially as adolescence is marked by rapid changes and heightened psychological challenges. This study aims to systematically review empirical findings on the role of trait emotional intelligence in adolescents’ mental well-being. The research employed a systematic review design guided by the PRISMA framework, focusing on articles published between 2015 and 2025 in Indonesian or English and involving adolescents aged 13–18. Searches were conducted across major scholarly databases, and fifteen studies met the inclusion criteria. The review indicates that trait emotional intelligence is generally associated with more adaptive psychological outcomes, including better stress management, reduced negative emotional states, and healthier social functioning. Several studies also highlight methodological concerns such as inconsistencies in measurement tools and varied findings across gender. Overall, the results emphasize the importance of trait emotional intelligence as a protective factor for adolescents’ mental well-being and suggest the need for future studies with stronger methodological alignment and more consistent measurement.